THE PROSPECTS OF IMPROVING DENTAL HEALTH CARE MANAGEMENT – A CASE STUDY BY THE "VUKADINOVIC" DENTAL PRACTICE, THE REPUBLIC OF SERBIA - Vukadinović, Aleksandra (Srpski medicinski časopis Lekarske komore, 2022)
Introduction: Dental medicine is a part of health care which is responsible for providing dental health care for the population of an area using all available means - by preserving, improving and establishing the specific functions and the appearance of the oral cavity and its individual parts, by studying and preventing common diseases of the mouth, as well as by treating diseases, disorders and mouth and dental injuries. The system of dental health care in the Republic of Serbia requires changes in the field of legislation and the organizational process, as well as financial investments for the purpose of improving the organizational process and achieving a greater number of professional staff that would provide dental services. The McKinsey 7S Model is a good tool for checking the managing abilities and the capacity of a certain organization to respond to the modern demands of its users. Aim: The aim of the paper was to investigate the prospects of improving the current dental health care management system. Methods: The method involves a case study on applying the McKinsey 7S diagnostic model to a private dental practice. Results: The results of the research served as the basis for proposing potential improvements to dental health care management.